Nampt: Linking NAD biology, metabolism, and cancer - Garten, Antje (2008)
Nicotinamide phosphoribosyltransferase (Nampt) converts nicotinamide to nicotinamide mononucleotide (NMN), a key NAD intermediate. Previously identified as a cytokine PBEF and controversially claimed as an insulin-mimetic hormone visfatin, Nampt has recently drawn much attention in different fields, including NAD biology, metabolism, and inflammation. As an NAD biosynthetic enzyme, Nampt regulates the activity of NAD-consuming enzymes such as sirtuins and influences a variety of metabolic and stress responses. Nampt also plays an important role in the regulation of insulin secretion in pancreatic β cells. Nampt appears to have another function as an immunomodulatory cytokine and plays a role in inflammation. This review summarizes these various functional aspects of Nampt and discusses its potential roles in diseases, including type 2 diabetes and cancer.